Burnout in South African dialysis practitioners: a mixed methods study - Chiba, Sheetal; Ajayi, Adekunle; Dayal, Chandni; Diana, Nina; Teckie, Gloria; Davies, Malcolm (African Journal of Nephrology, 2026)
Introduction: Provision of dialysis to patients with kidney failure relies on skilled dialysis practitioners (DPs), about whom little is known of the effect on burnout of workplace stressors, resource limitations, and the COVID-19 pandemic, which have increased the condition in other nursing specialities. We therefore analysed burnout in South African DPs working in the public sector. Methods: Sixty-four anonymous volunteers were recruited from three public sector treatment centres in Johannesburg. Burnout was assessed using the Maslach Burnout Inventory–Human Services Survey (MBI–HSS); the study population additionally completed surveys recording their workplace and COVID-19 experiences. The effect of respondent demographics, workplace, and pandemic experiences on burnout was determined using regression modelling. Results: Burnout occurred in 22%. Workplace challenges affected 97% of our sample; staffing shortages (97%), insufficient pay (75%), and perceived lack of management support (70%) were frequently cited. Sixty-four percent reported deteriorated perception of their career following COVID-19. Age (ß –0.29 ± 0.12, P = 0.015), longer time in current position (ß 0.38 ± 0.15, P = 0.012), lack of management support (ß 2.76 ± 0.93, P = 0.003), and lower career perception following COVID-19 (ß 3.68 ± 0.91, P < 0.001) increased emotional exhaustion; inadequate pay reduced personal sense of accomplishment (ß –1.12 ± 0.54, P = 0.036). Impaired career perception following COVID-19 independently increased burnout (OR 2.07, 95% CI 1.06–4.06, P = 0.033). Conclusions: Burnout rates in South African DPs are high and exceed those of many other regions. Perceived inadequate remuneration and poor management support are important factors underlying the condition. COVID-19 experiences continue to exert a significant effect on career appraisal and burnout.